Can alcohol control policies reduce cirrhosis mortality? An interrupted time‐series analysis in Lithuania. (30th January 2022) - Tran, Alexander; Jiang, Huan; Lange, Shannon; Manthey, Jakob; Štelemėkas, Mindaugas; Badaras, Robertas; Petkevičienė, Janina; Radišauskas, Ričardas; Room, Robin; Rehm, Jürgen
Abstract: Background and Aims: The relationship between alcohol consumption and cirrhosis is well established. Policies that can influence population‐level use of alcohol should, in turn, impact cirrhosis. We examined the effect of population‐level alcohol control policies on cirrhosis mortality rates in Lithuania – a high‐income European Union country with high levels of alcohol consumption. Methods: Age‐standardized, monthly liver mortality data (deaths per 100, 000 adults, aged 15+) from Lithuania were analysed from 2001 to 2018 (n = 216 months) while controlling for economic confounders (gross domestic product and inflation). An interrupted time‐series analysis was conducted to estimate the effect of three alcohol control policies implemented in 2008, 2017 and 2018 and the number of cirrhosis deaths averted. Results: There was a significant effect of the 2008 ( P  < .0001) and 2017 ( P  = .0003) alcohol control policies but a null effect of the 2018 policy ( P  = .40). Following the 2008 policy, the cirrhosis mortality rate dropped from 4.93 to 3.41 (95% CI: 3.02‐3.80) deaths per 100, 000 adults, which equated to 493 deaths averted. Further, we found that following the 2017 policy, the mortality rate dropped from 2.85 to 2.01 (95% CI: 1.50‐2.52) deaths per 100, 000 adults, corresponding to 245 deaths averted. Conclusions: Our findings support the hypothesis that alcohol control policies can have a significant, immediate effect on cirrhosis mortality. These policy measures are cost‐effective and aid in reducing the burden of liver disease.